Large-sized gladius-bearing octobrachians (coleoid cephalopods) in the Turonian plattenkalk of Vallecillo, Mexico. (November 2021) - Fuchs, Dirk; Stinnesbeck, Wolfgang
Abstract: The Turonian plattenkalk of Vallecillo (Mexico) yielded two large-sized gladiuses of octobrachian coleoids. The specimens determined as Boreopeltis ifrimae sp. nov. are both classified as members of the suborder Prototeuthina and represent the first coleoids from the Turonian of Mexico. Belemnoid coleoids are still unknown from Upper Cretaceous localities in Mexico. Boreopeltis ifrimae sp. nov. is the youngest representative of its genus. The occurrence of Boreopeltis in the northwestern Gulf of Mexico suggests a worldwide distribution in cold to warm temperate waters. The gladius (mantle) length of both specimens is remarkable and measures 470 mm, respectively. A general trend towards large and very large-sized coleoids is identified during the Late Cretaceous and began in the Turonian, as indicated by taxa from the southern Western Interior and the northern Gulf of Mexico. This gradual increase in octobrachian body sizes may reflect a commencing escalation in the arms race between coleoids, fishes, and marine reptilians.